Implementation of the Decision Support System for the Appointment of Permanent Employees at CV. Armas Suan Sejahatera Using the Analytical Hierarchy Process (AHP) Method - Muhammad Iqbal Panjaitan; Denni M. Rajagukguk; Mamed Rofendi Manalu (Jurnal Info Sains : Informatika dan Sains, 2023)
The development of information technology today requires fast and accurate information in its implementation. Appointment of employees who perform well with the support of a decision support system is one implementation of the development of information technology. Research that uses the AHP method in this decision support system produces an appointment decision support system application that can be used in companies. The criteria used in this employee hiring decision support system are: Quality of employee work. The results of this study are to produce a ranking order of the selected good performing employee candidates, and the output of the application can assist decision makers in selecting alternative employee appointments. The application in this study is implemented using the VB programming language. NET 2008 and the database uses MySQL. The Analytical Hierarchy Process (AHP) method is a method used in designing decision support systems. The concept used by the AHP method is to change the value of a qualitative Decision Support System into a quantitative value. So that the decisions taken can be more objective. By using the Analytical Hierarchy Process, it is hoped that the process of hiring employees will be more effective and efficient so that company leaders quickly get the value of employees who will be appointed as permanent employees to get the expected results.